UNIVERSITY-INDUSTRY PARTNERSHIPS FOR INNOVATION: SRI LANKAN EXPERIENCES - WEERASINGHE, Rukmal Nishantha; JAYAWARDANE, Ananda KW (Annals of Spiru Haret University. Economic Series, 2018)
The University sector in the national innovation system (NIS) is considered as one of the key players which links new knowledge with the industry for the purpose of diffusing new knowledge for economic and social benefits through commercialization of products, services, processes and other artifacts. This paper inquires the role of Sri Lankan universities in the innovation process by paying special attention on the strength of university-industry linkages. Responses from the industrial sector obtained through a surveys and interviews with respondents. Data presented and analyzed through descriptive statistics using summery statistics and figures. Social Network Analysis (SNA) was employed to determine the strength of the networking relationship among the Universities and the Firms Qualitative data were analyzed employing the method of content analysis. The study revealed a positive trend in the higher education sector towards performing effective role in the future towards innovation. However, it was evident that these relationships are still remained very weak. The industrial sector remains inward oriented with little intention to innovation while universities still prioritize their traditional teaching role in higher education.